2011
DOI: 10.1007/s00586-011-1915-2
|View full text |Cite
|
Sign up to set email alerts
|

The IL-1β (+3953 T/C) gene polymorphism associates to symptomatic lumbar disc herniation

Abstract: Carriers of the CC genotype of the IL-1β (+3953 T/C) SNP were more frequent among LDH patients suggesting some potential role of the IL-1β SNP on LDH pathogenesis. The eNOS (-786 T/C) and iNOS (22 G/A) SNPs were more frequent among the control subjects, suggesting their possible protective role against LDH. Genotyping these SNPs could be useful to identify persons with an increased lifetime risk of disc herniation in whom measures to avoid LDH could be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…Moreover, the population studied by us in Mexico has a particular genetic background, since half of the most common haplotypes found in this population have a proposed European origin, most likely from Spanish origin [ 52 ]. Not surprisingly, the frequency of the T allele in our population (28.0%) was similar to the one observed in a Spanish population (35.5%) [ 49 ] and alike our results was not associated with IDD.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the population studied by us in Mexico has a particular genetic background, since half of the most common haplotypes found in this population have a proposed European origin, most likely from Spanish origin [ 52 ]. Not surprisingly, the frequency of the T allele in our population (28.0%) was similar to the one observed in a Spanish population (35.5%) [ 49 ] and alike our results was not associated with IDD.…”
Section: Resultssupporting
confidence: 90%
“…A study of a Danish population also found an association of this polymorphism with disc degeneration [ 39 ]. In contrast, a case-control study of a population of Spain found no association between T allele and symptomatic lumbar disc herniation [ 49 ]. The reason for this inconsistent association between the T allele and IDD may be due to ethnic differences in the studied populations, or by different haplotypes in the promoter or enhancer regions.…”
Section: Resultsmentioning
confidence: 99%
“…1,10,15,22 Increasing polymorphisms in gene encoding for these factors have been reported in lumbar disc diseases and LBP, and, in particular, the SNP of IL-1b may confer susceptibility to LBP. 11,18,20,25 Caspase-9 is an initiator caspase protease for apoptosis, and recent studies have indicated that it plays a significant role in apoptosis in human intervertebral disc degeneration. 17,19 Caspase-9 polymorphism has been reported to be associated with the susceptibility to discogenic LBP.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…Genotypes were determined by PCR-RFLP using a Hightech Thermocycler Cycler-Technology for Life (SensoQuest, Gottingen, Germany). Protocols for -889T>C IL-1α, -31T>C and -511C>T IL-1β, -330 T>G IL-2 and -174 G>C IL-6 polymorphisms followed previously described PCR-RFLP techniques (Todhunter et al, 2005;Gao, 2009;Paz Aparicio et al, 2011;September et al, 2011) (see Table 1).…”
Section: Methodsmentioning
confidence: 99%